2018
DOI: 10.1038/s41598-018-31708-8
|View full text |Cite
|
Sign up to set email alerts
|

Systems pharmacology-based exploration reveals mechanisms of anti-steatotic effects of Jiang Zhi Granule on non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD), which is in parallel with the obesity epidemic, accounts for a large amount of all chronic liver disease. Jiang Zhi Granule (JZG), a clinically used herbal formula, is developed in accordance with traditional Chinese medicine (TCM) pathogenesis for treating patients with NAFLD. In previous studies, the anti-steatotic effects of JZG against NAFLD have been demonstrated, and in this study, a systems pharmacology approach was used to explore the pharmacological mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In Chinese clinical practice, TCM has unique advantages in the clinical treatment of NAFLD, and most patients with NAFLD received TCM treatment. TCM stresses the differentiation treatment [8]. In other words, there are different types of syndromes in different patients with NAFLD, thus, different prescriptions need to be adopted for each specific treatment.…”
Section: Breakthroughs In Prevention and Treatment With Tcmmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chinese clinical practice, TCM has unique advantages in the clinical treatment of NAFLD, and most patients with NAFLD received TCM treatment. TCM stresses the differentiation treatment [8]. In other words, there are different types of syndromes in different patients with NAFLD, thus, different prescriptions need to be adopted for each specific treatment.…”
Section: Breakthroughs In Prevention and Treatment With Tcmmentioning
confidence: 99%
“…As regards traditional Chinese medicine (TCM), its pathogenesis mainly includes stagnation of liver-qi and catharsis disorder, leading to hindrance of functional activities of qi, liver-qi perversion attacking the stomach, qi disease involving blood, and poor blood flow, which finally induce NAFLD [7]. Chinese and international scholars agree that NAFLD is caused by multiple factors including insulin resistance, lipid metabolism disorder, and oxidative stress in Western medicine [8].…”
Section: Introductionmentioning
confidence: 99%
“…It can predict the active compounds within the herbal formula JZG and their corresponding therapeutic targets and synergistic effects. The analysis has highlighted a number of signaling pathways that may be involved in therapeutic effects of JZG, they are ER-phagosome pathway, proteasomal ubiquitindependent protein catabolic process, TRAF6-mediated induction of pro-inflammatory cytokines, MAPK cascade, regulation of lipid metabolism including steroid biosynthesis, cholesterol transport and fatty acid metabolism (116). Indeed, mechanistic study also shows that JZG regulates lipid metabolism.…”
Section: Combining Ancient Wisdom and Modern Science To Explore Herbamentioning
confidence: 99%
“…JZG also protects mitochondrial integrity against oxidative stress in the hepatocyte model (121). In the mouse model of NAFLD, JZG reduces hepatic lipid content and ameliorates inflammation, improves metabolic disorder and reduces liver injury (116,118,121). In CCl4-induced liver injury in NAFLD rat, JZG also significantly reduces hepatic inflammation, ER stress, hepatic necrosis, hepatic lipid, blood transaminases and blood lipids (122).…”
Section: Combining Ancient Wisdom and Modern Science To Explore Herbamentioning
confidence: 99%
“…Epidemiological researches have reported that NAFLD is one of the three main causes of cirrhosis [4], and NASH is rapidly becoming the leading cause of end-stage liver disease [5,6]. However, except for lifestyle interventions, such as exercise and dietary, there is still no approved pharmacotherapy for NAFLD.…”
Section: Introductionmentioning
confidence: 99%